2021
DOI: 10.3390/ijerph18063026
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Social Isolation during the COVID-19 Pandemic on Physical and Mental Health: The Lived Experience of Adolescents with Obesity and Their Caregivers

Abstract: Adolescence is a complex developmental phase, made more complex by obesity and the social isolation imposed by the COVID-19 pandemic. The literature related to the impact of social isolation on obesity self-management in adolescents is scant and inconsistent. This paper describes the phenomenon from the perspectives of a sample of adolescents with obesity enrolled in an inpatients’ multidisciplinary rehabilitation program for weight-loss and their caregivers, and its impact on different life domains. Individua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(49 citation statements)
references
References 85 publications
0
42
0
2
Order By: Relevance
“…The trial will be conducted within the context of a three-week in-hospital multidisciplinary rehabilitation program for weight loss based on nutritional, physical, and psychological rehabilitation [ 50 , 51 , 52 ], according to the Italian National Health System recommendations. As part of the nutritional program, adolescents will be assessed by a staff dietician and placed on an individualized hypocaloric diet composed of 53% carbohydrates, 26% fat, and 21% protein [ 53 ] and a fluid intake of at least 1500 mL per day −1 .…”
Section: Methodsmentioning
confidence: 99%
“…The trial will be conducted within the context of a three-week in-hospital multidisciplinary rehabilitation program for weight loss based on nutritional, physical, and psychological rehabilitation [ 50 , 51 , 52 ], according to the Italian National Health System recommendations. As part of the nutritional program, adolescents will be assessed by a staff dietician and placed on an individualized hypocaloric diet composed of 53% carbohydrates, 26% fat, and 21% protein [ 53 ] and a fluid intake of at least 1500 mL per day −1 .…”
Section: Methodsmentioning
confidence: 99%
“…In line with previous research [8,44,80], due to the impossibility of using routinely paper-and-pencil assessment questionnaires, an ad hoc structured interview was created for this study and administered to oncological outpatients. The use of a structured interview was deemed appropriate to allow the investigation of the patients' thoughts, emotions, and psychological issues using standardized methodological procedures [8].…”
Section: Measures: (Development Of) the Structured Interviewmentioning
confidence: 99%
“…In line with previous studies [80], the pool of items of the structured interview was developed using a two-step procedure [46,[81][82][83][84].…”
Section: Measures: (Development Of) the Structured Interviewmentioning
confidence: 99%
“…This shows that social health has a positive impact on adolescents, even during the pandemic. Although many studies argued that adolescents' physical and mental health is at risk [11][12][13][14][15][16][17][18][19][20][21][22], we observed that online and in-person hybrid PE classes promote adolescents' social healthy by lowering alienation in PE and boosting school happiness and future healthy life expectancy. To ensure adolescents' social health during the COVID-19 pandemic, Kim's (2005) [30] strategies to resolve the issue of alienation in PE should be utilized.…”
Section: Discussionmentioning
confidence: 51%
“…Furthermore, studies also note that adolescents have experienced a decline in their physical health. COVID-19 led to a spike in the prevalence of obesity among adolescents [16], diminished participation in physical activities [17][18], and lowered the level of physical activity involvement [19]. In addition, studies have also reported that adolescents showed a deteriorated health-related quality of life (HRQoL) [20] and poorer lifestyle habits [18,21,22].…”
Section: Introductionmentioning
confidence: 99%